2022
DOI: 10.3389/fendo.2022.975623
|View full text |Cite
|
Sign up to set email alerts
|

A novel ferroptosis-related gene prognostic index for prognosis and response to immunotherapy in patients with prostate cancer

Abstract: BackgroundProstate cancer (PCa) is among the leading causes of cancer death worldwide. Ferroptosis refers to an iron-dependent form of regulated cell death and is involved in prostate tumorigenesis. A few ferroptosis-related gene signatures have been developed to predict the prognosis for PCa patients. However, previous signatures were typically established based on biochemical recurrence-free survival, which has proven not to be a good surrogate for overall survival (OS). This study aimed to construct a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Recent studies have discovered that Jak2V617F, ALOX5, and NCF2 are involved in the formation of atherosclerosis by regulating macrophage ferroptosis [ 38 , 39 ]. Furthermore, the important role of macrophage-mediated ferroptosis in cancer therapy has also been widely researched [ 40 , 41 ]. In colorectal cancer, there is a crosstalk between ferroptosis and three other programmed cell deaths, including necrosis, autophagy, and apoptosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have discovered that Jak2V617F, ALOX5, and NCF2 are involved in the formation of atherosclerosis by regulating macrophage ferroptosis [ 38 , 39 ]. Furthermore, the important role of macrophage-mediated ferroptosis in cancer therapy has also been widely researched [ 40 , 41 ]. In colorectal cancer, there is a crosstalk between ferroptosis and three other programmed cell deaths, including necrosis, autophagy, and apoptosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis-related genes as biomarkers Wang et al [161], Liu et al [162], and Lu et al [163] constructed different prostate cancer risk prediction models based on four (E2F1, CDC20, TYMS and NUP85), seven (AKR1C3, ALOXE3, ATP5MC3, CARS1, MT1G, PTGS2 and TFRC), and nine (AIFM2, AKR1C1, AKR1C2, CBS, FANCD2, FTH1, G6PD, NFS1 and SLC1A5) ferroptosis-related genes (FRG), respectively. The results showed that high FRG scores patients had poorer clinicopathological features, higher likelihood of biochemical recurrence and worse prognosis.…”
Section: Ferroptosis and Drug Resistancementioning
confidence: 99%
“…Although studies on the regulation of ferroptosis in prostate cancer are frequently reported and showed a good therapeutic prospect, the real application of ferroptosis in clinical treatment needs both in vivo experiment validation and multi-demonstration. Surprisingly, ferroptosis can predict disease-free survival (DFS) and immunotherapy response for PCa patients following radical prostatectomy in addition to killing cancer cells [25,26]. In addition, by comparing the data of whole genome patients, Li et al [27], they were found that the characteristics of genomic changes in Chinese patients were significantly different from those in western populations, and the mutations or deletions of these genes may have other effects on the occurrence of ferroptosis.…”
Section: Ferroptosis and Prostate Cancermentioning
confidence: 99%